Mindfulness meditation in residential aged care: what frail older people identified as beneficial for their spiritual care and well-being - Steller, Beate (Journal of religion, spirituality & aging, 2023)
Spiritual care in Residential Aged Care (RAC) is primarily concerned with meaning-making and residents’ wellness. This qualitative study evaluated what older people living in RAC thought were the benefits of participating in a mindfulness meditation group and how it enhanced spiritual growth/wellbeing. Thirteen residents attended a six-week group program and were interviewed at the beginning and end of the program. Four (4) themes were identified: 1) meaningfully connecting and sharing, 2) providing a supportive and reflective space, 3) practising mindfulness-meditation and 4) practising and expressing gratitude. Findings inform the provision of better emotional/spiritual support and invite further research.